2019
DOI: 10.1002/chem.201900851
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer IrIII–Aspirin Conjugates for Enhanced Metabolic Immuno‐Modulation and Mitochondrial Lifetime Imaging

Abstract: The chemo‐anti‐inflammatory strategy is attracting ever more attention for the treatment of cancer. Here, two cyclometalated IrIII complexes Ir2 and Ir3 formed by conjugation of Ir1 with two antiphlogistics (aspirin and salicylic acid) have been designed. Ir2 and Ir3 exhibit higher antitumor and anti‐inflammatory potencies than a mixture of Ir1 and aspirin/salicylic acid. We show that they can be hydrolyzed, accumulate in mitochondria, and induce mitochondrial dysfunction. Due to their intense long‐lived phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 63 publications
0
20
0
2
Order By: Relevance
“…In addition, cyclometalated iridium complexes are another type of anti-cancer agent acting on functional mitochondria ( Figure 4 ). Mao et al reported several representative cyclometalated iridium complexes with anti-cancer activity through loss of mitochondrial membrane potential and elevation of intracellular ROS, such as iridium complexes 17 and 18 [ 103 , 104 ]. For 17 , the ubiquitin-proteasome system (UPS) was also induced and resulted in the collapse of mitochondria and subsequent cytoplasmic vacuolation because of the rapid loss of mitochondrial functions [ 103 ].…”
Section: Anti-cancer Metal Complexes Activating Ros-mediated Signaling From Mitochondriamentioning
confidence: 99%
“…In addition, cyclometalated iridium complexes are another type of anti-cancer agent acting on functional mitochondria ( Figure 4 ). Mao et al reported several representative cyclometalated iridium complexes with anti-cancer activity through loss of mitochondrial membrane potential and elevation of intracellular ROS, such as iridium complexes 17 and 18 [ 103 , 104 ]. For 17 , the ubiquitin-proteasome system (UPS) was also induced and resulted in the collapse of mitochondria and subsequent cytoplasmic vacuolation because of the rapid loss of mitochondrial functions [ 103 ].…”
Section: Anti-cancer Metal Complexes Activating Ros-mediated Signaling From Mitochondriamentioning
confidence: 99%
“…[90] . 阿司 匹林与 Ir 配合物反应制得金属衍生物 102, 其在 PC3、 CT26、HT29 癌细胞中的 IC 50 值分别为(4.5±0.5)、 (4.4±0.7)和(2.8±0.3) μmol•L -1 , 具有抗癌活性 [91] . [93] .…”
Section: 类似地 在水杨醛和阿司匹林的基础上合成了四种unclassified
“…As multifunctional ligands, SA and AS are attracting ever more attention for the treatment of cancer. For instance, the research of Wu et al demonstrated that conjugation of SA or AS to the Ir(III) moiety could improve the cellular uptake efficacies of the Ir(III) complexes and achieve a high synergistic effect [ 19 ]. Liu and Dhar et al reported that a novel Pt(IV) prodrug of cisplatin, asplatin, with the ligation of aspirin ( c , c , t -[PtCl 2 (NH 3 ) 2 (OH) (aspirin)]), demonstrated significantly higher cytotoxicity than cisplatin towards tumor cells and nearly completely overcame the drug resistance of cisplatin-resistant cells [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%